Structures Congress 2012 2012
DOI: 10.1061/9780784412367.200
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Vibration Measurements of Dynamic Properties of School Buildings in Montreal, Quebec

Abstract: As part of a research project conducted at McGill University, in-situ dynamic properties of 80 low-rise school buildings located in Montreal, Quebec, were identified from ambient vibration measurements. Natural periods determined for the two most common lateral load resisting systems (concrete shear wall buildings and concrete frame buildings with unreinforced masonry infill walls) are presented. They are compared to approximate equations that estimate the fundamental period as a function of building height, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…To evaluate the impact of soil ISFH, a structure with a seismic resisting force system (SRFS) consisting of a moment-resisting concrete frame with masonry infill walls was considered. The periods of such a structure can be estimated based on Tischer’s (2012) work using Equation 6, where h n is the height of the structure.…”
Section: Part 1: Isfh Analysis Resultsmentioning
confidence: 99%
“…To evaluate the impact of soil ISFH, a structure with a seismic resisting force system (SRFS) consisting of a moment-resisting concrete frame with masonry infill walls was considered. The periods of such a structure can be estimated based on Tischer’s (2012) work using Equation 6, where h n is the height of the structure.…”
Section: Part 1: Isfh Analysis Resultsmentioning
confidence: 99%
“…9,35 To define seismic design levels for Canadian buildings, a comprehensive approach has been used according to Level 2 of the Canadian NRC-SQST-part 2 guideline and related conducted studies. 16,19,[36][37][38] In NRC-SQST-part 2, two different editions for building codes are considered as threshold versions: "pre-code edition" and "benchmark NBC edition." Although specific seismic provisions for strength and ductility were not adopted in the "pre-code edition," the "benchmark NBC edition" includes substantial improvements in seismic design requirements.…”
Section: Seismic Design Code Levelsmentioning
confidence: 99%
“…40 Therefore, the 1970 threshold year was considered a more appropriate year for the "pre-code edition" based on the recommendation from previous studies in Eastern Canada. 37,38,41 On the other hand, the 2005 NBCC can be defined as the "benchmark NBC edition," as it was incorporated with major changes, such as presenting a uniform hazard spectrum and introducing ductility-related force modification factors and overstrength-related force modification factors. 41,42 Based on these two editions, it can be concluded that buildings in Eastern Canada designed before the 1970 NBCC can be classified as pre-code buildings; however, the buildings designed after the 2005 NBCC can be considered as post-benchmark buildings and ones designed between 1970 and 2005 can be regarded as pre-benchmark buildings.…”
Section: Seismic Design Code Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seismic performance of schools deserves special attention because of their unique occupancy characteristics and important post-earthquake role. Past experience has shown that school buildings are especially vulnerable to earthquakes because of irregular structures, old buildings, inadequate exit way, non- structural falling objects, etc (Tischer, 2012). Rodgers (2012) reported more the 30 school building collapse in the different seismic events around the world, and 10,000 children lost their lives from 1963 to 2010.…”
Section: Introductionmentioning
confidence: 99%